Mixed-methods reproductive health knowledge, attitudes and practices survey of IDPs, returnees and host communities in Jonglei State, South Sudan - William Clemmer; Mounir Lado; Lynn Lieberman Lawry; Rachel Gabor; Jacques Katele; Lazarus Baak Madut; Katina Sommers; David Manuel; Claire Nadolski; Tracey Koehlmoos (BMJ Open)
Objectives To understand the current state of maternal, newborn and child health (MNCH) among internally displaced persons (IDPs), returnees and host communities in remote counties of Jonglei state.Design Cross-sectional, randomly sampled, mixed-methods, population-based household study.Setting Ayod, Nyirol, Fangak and Pigi counties of Jonglei, South Sudan.Participants 859 households, including 586 adult females and 273 adult males.Primary and secondary outcome measures Knowledge, attitudes and practices of MNCH. Secondary: contraception, pregnancies, pregnancy outcomes, use or non-use of antenatal care (ANC)/postnatal care (PNC), use of skilled birth attendants, breastfeeding, knowledge of warning or danger signs of pregnancy, gender-based violence (GBV) and MNCH attitudes/cultural norms.Results A total of 859 households consented to the study (586 females and 273 males) with a response rate of 96% among females and 94% among males. The ability to list at least three warning/danger signs or essentials of care for different MNCH categories among respondents was low (range, 37·0%–47·1%). 1% of females and 3% of males use contraception. ANC and PNC are suboptimal and largely provided by unskilled providers. 26% of women exclusively breastfed for up to 6 months. For respondents with children<2 years of age, 68·9% (95% CI 64·7 to 72·7) had received three doses of Penta valent vaccine. Females and males reported similar lifetime GBV rates.Conclusion Conflict and flooding in the remote survey areas are significant barriers to MNCH. Evidence-based interventions that decrease mortality and morbidity are lacking and the dearth of skilled health providers and healthcare facilities limits improvements in MNCH. Establishing cost-effective and evidence-based interventions proven to reduce MNCH mortality either at fixed facilities and/or in combination with mobile clinics and community outreach are necessary to ensure that IDPs and returnees are reached.